Diversidade e distribuição de Collembola (Arthropoda, Hexapoda) no Estado da Paraíba, Brasil: a influência dos fatores ambientais e espaciais e a descrição de novos táxons - Ferreira, Aila Soares (2018)
One of the main objectives of biodiversity research is to comprehend the distribution patterns of species, identifying the scaled in which ecological processes occur. The aim of this study is to characterize the Collembola assemblage in Caatinga and Atlantic Forest environments in Paraíba, evaluating how the spatial and environmental characteristics influence species richness, abundance and faunal composition; as well as evaluating the performance and complementarity of three sampling methods for edaphic Collembola fauna; and lastly, describe new species. The study was conducted in eight areas in the state of Paraíba. Samplings were performed during rainy season, choosing 10 points in each area distant 100m from each other. The specimens were collected using entomological aspirator, pitfall traps and Winkler extractor. The Partial Redundancy analysis (pRDA) with additive partitioning was used to determine the relative influence of environmental and spatial variables on assemblage composition. The Non-Metric Dimensional Scaling (NMDS) was used to describe and interpret the main gradients that exerted influence over the composition of the Collembola assemblies. To verify the complementarity of the sampling methods, NMDS analysis were performed for dry and humid forest areas, and a non-parametric Analysis of Variance with permutations (PERMANOVA) to compare between methods. A total of 28,382 springtail individuals, distributed in 69 species, 37 genera and 13 families were captured. The environmental and spatial variables explained 68% of the variation in faunal composition, with 28% explained by the environmental component, 12% by the spatial component, and 28% by a shared component. The NMDS revealed two distinct groups, one formed by the humid forest areas, and the other by the dry forests, possibly revealing a lack of connectivity between the two environments. Thus, the spatially structured environmental variables were determinants of the faunal composition for Collembola. Pitfall traps were the method with the best performance in all analyzed parameters, being indicated as the sampling method for Collembola in humid and dry forest areas. Three new species from the genus Denisiella were described for Brazil. The tibiotarsus of the male specimens of Denisiella presented different structures, revealing important taxonomic characteristics.